Soldier of change : from the closet to the forefront of the gay rights movement - Snyder-Hill, Stephen (Potomac Books, an imprint of the University of Nebraska Press, 2014)
When ""Don''t Ask, Don''t Tell, "" the official U.S. policy on gays serving in the military, was repealed in September 2011, soldier Stephen Snyder-Hill (then Captain Hill) was serving in Iraq. Having endured years of this policy, which passively encouraged a culture of fear and secrecy for gay soldiers, Snyder-Hill submitted a video to a Republican primary debate (held two days after the repeal). In the video he asked for the Republicans'' thoughts regarding the repeal and their plans, if any, to extend spousal benefits to legally married gay and lesbian soldiers. His video was booed by the au